Penegakan Sanksi Kode Etik Profesi Kepolisian Terhadap Anggota Polri Melakukan Pungutan Liar - Gatot Priadi (Albayan Journal of Islam and Muslim Societies, 2024)
Police officers who commit extortion crimes have violated disciplinary rules and the code of ethics because every member of the Police is obliged to uphold the law and maintain the honor, reputation, and dignity of the Indonesian National Police. The formulation of the problem in this study is how to regulate the law on extortion committed by members of the Traffic Police Unit, how is the accountability of members of the Traffic Police Unit who commit extortion, how to resolve violations of the code of ethics of the Traffic Police Unit who commit extortion. This study is a descriptive analytical study that leads to empirical legal research. The data sources in this study are primary data and secondary data. Primary data is data obtained directly from research at the North Sumatra Regional Police. Data collection tools are library research and field research. The legal regulation of extortion carried out by members of the Traffic Police Unit is regulated in Law Number 2 of 2002 concerning the Republic of Indonesia Police, Law Number 20 of 2001 concerning Corruption Crimes, Presidential Regulation (Perpres) Number 87 of 2016 concerning the Task Force for Eradicating Extortion (Saber Pungli) and the Criminal Code. The weakness of this law is that it does not explicitly regulate sanctions against perpetrators of extortion crimes. The accountability of members of the Traffic Unit who carry out extortion, the North Sumatra Regional Police will take strict action against its members who are proven to have carried out extortion in carrying out services to the community, namely being removed from their positions and not being allowed to carry out traffic duties in the field and being assigned as Casual Daily Employees (PHL). The resolution of violations of the code of ethics of the North Sumatra Regional Police Traffic Unit who carry out extortion is by forming a special team (Timsus) tasked with eradicating police members who carry out extortion (Pungli) while carrying out state duties. This team is tasked with monitoring member activities at the internal and external police levels.